Predictive Factors of the Burnout Syndrome Occurrence in the Healthcare Workers During the COVID-19 Pandemic - Grigorescu, Simona; Cazan, Ana-Maria; Rogozea, Liliana; Grigorescu, Dan Ovidiu (Frontiers in Medicine, 2022)
The coronavirus disease 2019 (COVID-19) pandemic is probably the most critical epidemiological situation that human civilization has faced in the last few decades. In this context, of all the professional categories involved in the management of patients with COVID-19 are the most likely to develop burnout syndrome. The main objective of this study is to analyze specific predictive factors of the occurrence and development of the burnout syndrome in the healthcare workers involved in the diagnosis and treatment of patients with COVID-19. The study focused on determining factors of the occurrence, development and maintaining the specific burnout syndrome related to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic infection. The study was conducted on a sample of 959 participants, medical personnel from all the public medical entities in Romania(including 5 hospitals): 122 male and 755 female (82 participants did not declare their gender), with a mean age of 42.29 years (SD = 9.97). The sample included 219 doctors, 477 nurses, 214 auxiliary medical personnel and 49 other types of hospital workers. A cross-sectional design was used. Three predictors of the burnout syndrome were identified: Work conditions, Fear of the consequences (including death) determined by the COVID-19 and Need for emotional support. Meaning of work had a moderating role. Several moderated mediation models were tested. The indirect relationship of Work conditions with burnout via Fear of infection was statistically significant; in addition, the indirect effect of Work conditions on burnout through both fear of infection and need for support was statistically significant. The moderation analysis showed that Meaning of work buffer the relationship between Work conditions and Fear of infection. The variance explained by the model including the moderator (30%) was higher than the variance explained by Model 1 (27%), showing that adding the moderating effect of Meaning of work to the relationship of Work conditions with burnout was relevant. The results could be used to design specific interventions to reduce the occurrence of the burnout syndrome in healthcare workers, the implementation of a strategy to motivate employees by highlighting and recognizing the high significance of the work of those in the frontline of the fight against COVID-19.